2001
DOI: 10.1086/319202
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Sexually Transmitted Diseases in Human Immunodeficiency Virus-Positive Patients in Peru Reveals an Absence of Chlamydia trachomatis and Identifies Trichomonas vaginalis in Pharyngeal Specimens

Abstract: To determine the prevalence of sexually transmitted diseases (STDs), we screened 107 human immunodeficiency virus-positive patients in Peru, where the virus is predominantly sexually transmitted. Patients had multiple risk factors for STDs, and 38% of women and 50% of men had at least 1 STD (gonorrhea, trichomoniasis, herpes simplex, anogenital warts, or syphilis seropositivity). No chlamydial infection was detected, even though infection rates in the general population are 5%-12%. Patients receiving trimethop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…1-4 8 9 However, recent reports on the presence of trichomonads in non-traditional sites, with the use of molecular diagnostic methods, indicate otherwise. [21][22][23][24] The difficulty in morphological differentiation of trichomonads has also been highlighted in veterinary medical practice. Romatowski 25 initially reported isolating P hominis from the gut of kittens.…”
Section: Discussionmentioning
confidence: 99%
“…1-4 8 9 However, recent reports on the presence of trichomonads in non-traditional sites, with the use of molecular diagnostic methods, indicate otherwise. [21][22][23][24] The difficulty in morphological differentiation of trichomonads has also been highlighted in veterinary medical practice. Romatowski 25 initially reported isolating P hominis from the gut of kittens.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low cost and low toxicity are their principle advantages [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The same study revealed a 1.5% T. vaginalis detection rate from rectal swabs collected from a group of 952 women. An initial assessment of T. vaginalis extraurogenital detection in men (33) revealed that 3 of 70 human immunodeficiency virus-positive individuals had detectable pharyngeal T. vaginalis by PCR. Two of the men were asymptomatic at the time of specimen collection, and all acknowledged a history of orogenital sexual activity.…”
Section: Discussionmentioning
confidence: 99%